2006
DOI: 10.2170/physiolsci.rp012406
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Motion after Thixotropy Conditioning of Inspiratory Muscles in Healthy Humans

Abstract: Abstract:Inspiratory muscle conditioning at a lower or higher lung volume based on the principles of muscle thixotropy causes acute changes in end-expiratory chest wall and lung volumes. The present study aimed to demonstrate the time course of effects of this conditioning on both end-expiratory chest wall volume and thoracoabdominal synchrony. We measured chest wall motion with respiratory induction plethysmography at 0.5, 1, 2, 3, and 6 min after conditioning at three different lung volumes in 15 healthy men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The decreases in end‐expiratory and end‐inspiratory Vcw after conditioning at RV 10 were shared by the rib cage and abdominal compartments, which is consistent with previous findings under resting conditions 9 . However, under CPAP, the rib cage deflation was clearly larger than the abdominal deflation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The decreases in end‐expiratory and end‐inspiratory Vcw after conditioning at RV 10 were shared by the rib cage and abdominal compartments, which is consistent with previous findings under resting conditions 9 . However, under CPAP, the rib cage deflation was clearly larger than the abdominal deflation.…”
Section: Discussionsupporting
confidence: 90%
“…After conditioning at FRC 10 , however, changes in end‐expiratory Vcw under CPAP were not significant. It has previously been shown that conditioning at FRC during resting breathing has little effect on end‐expiratory Vcw of the respiratory system 7–9 . These findings suggest that the relative length of inspiratory muscles at the time of conditioning is a factor that influences inspiratory muscle thixotropy.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations